Kolaborasi Orang Tua dengan Guru dalam Memotivasi Belajar Siswa Sekolah Dasar pada Pembelajaran Jarak Jauh - Pebriyona, Eno Ropilin; Fahrurrozi, Fahrurrozi; Sari, Yofita; Hasanah, Uswatun (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to analyze the collaboration between parents and teachers in motivating elementary school students to learn distance learning. This research is a descriptive qualitative research with a literature study approach. The results of data analysis show that collaboration between parents and teachers is very important in an effort to motivate elementary school students to learn distance learning. Based on the results of the data analysis above, it can be concluded that to increase the motivation of elementary school students in participating in distance learning, the role of teachers and parents is needed. So, teachers and parents can work together to guide and direct children in learning. So that children will be motivated to participate in distance learning optimally. From these conclusions, the impact resulting from this study is known that the importance of collaboration between parents and teachers in motivating elementary school students' learning in distance learning.